Socioeconomic differences in coronary procedures and survival after out-of-hospital cardiac arrest: A nationwide Danish study. (August 2020) - Møller, Sidsel; Wissenberg, Mads; Kragholm, Kristian; Folke, Fredrik; Hansen, Carolina Malta; Ringgren, Kristian B.; Andersen, Julie; Barcella, Carlo; Lippert, Freddy; Køber, Lars; Gislason, Gunnar; Gerds, Thomas Alexander; et al.
Abstract: Aim: It remains unclear whether socioeconomic differences exist in post-resuscitation care in out-of-hospital cardiac arrests (OHCA). We aimed to examine socioeconomic differences in coronary procedures and survival after OHCA. Methods: OHCA patients ≥30 years of cardiac cause with a hospital admission from the Danish Cardiac Arrest Registry, 2001–2014, were divided according to quartiles of household income (lowest, low, high, highest). Associations of income, coronary procedures and 30-day survival were examined by age-standardized incidence rates and incidence rate ratios (IRR), and by logistic regression. Results: A total of 6105 patients were included. Higher-income patients were younger, males and had less comorbidity-burden. Higher-income patients had higher incidence rates for coronary angiographies both day 0–1 and day 2–7 after OHCA (day 0–1: highest: IRR 1.79, 95%CI 1.46–2.21; high: IRR 1.28, 95%CI 1.10–1.51; low: IRR 1.05, 95%CI 0.90–1.23), compared to lowest. Fifty-four percentage of the patients undergoing a coronary angiography received percutaneous-coronary-intervention or coronary-artery-bypass-grafting with no difference among three of the four groups, but lower IRR in low-income patients (IRR 0.74, 95%CI 0.61–0.89) compared to lowest. Higher-income patients had also higher odds for 30-day survival compared to lowest, both in patients with (highest: OR 1.61, 95%CI 1.12–2.32; high: OR 1.13, 95%CI 0.80–1.60; low: OR 1.14, 95%CI 0.81–1.61) and without (highest: OR 2.54, 95%CI 1.83–3.53; high: OR 1.41, 95%CI 1.06–1.87; low: OR 1.12, 95%CI 0.86–1.47) coronary angiography day 0–1. Conclusion: Higher-income patients were found associated with more performed coronary angiographies after OHCA, and higher odds for 30-day survival.